Free Trade and Weak States: The Case of Dr-Cafta in Nicaragua - Runyon, Molly (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: DR-CAFTA presents wonderful opportunities for the people and states of Central America. Unfortunately, the government of Nicaragua is in very bad shape and is unlikely to implement the complementary policies necessary to support the 'losers' in globalization in the transition. This paper looks at the four branches of government in Nicaragua and compares them to an idealized government.